Method for manufacturing a carrier transport film, light emitting diode

By using titanium dioxide nanocrystals and subjecting them to thermal hydrogen reduction, a carrier transport thin film with oxygen-rich vacancies on its surface was prepared. This solved the problems of nonradiative Auger recombination and material limitations in zinc oxide carrier transport thin films, thereby improving electron transport performance and overall device performance.

CN114695699BActive Publication Date: 2026-11-06TCL TECHNOLOGY GROUP CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011630443.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-30
Publication Date
2026-11-06
Estimated Expiration
2040-12-30

AI Technical Summary

Technical Problem

Existing zinc oxide carrier transport films suffer from nonradiative Auger recombination caused by excess electron injection. Furthermore, when zinc oxide nanoparticles are used as electron transport layer materials, the materials, preparation conditions, and dissolution solvents of other layer structures in the device are limited.

Method used

Titanium dioxide nanocrystals were used as the carrier transport material, and a carrier transport thin film was prepared by thermal hydrogen reduction treatment in a hydrogen atmosphere to form an electron transport layer with oxygen-rich vacancies on the surface.

Benefits of technology

This improved electron mobility and conductivity, enhanced charge transport performance at the bulk phase and interface, solved the limitation problem of zinc oxide nanoparticles, and optimized the structure and fabrication method of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114695699B_ABST
    Figure CN114695699B_ABST
Patent Text Reader

Abstract

This invention relates to the field of carrier transport thin film technology and provides a method for preparing a carrier transport thin film. The invention provides a carrier transport material in the thin film comprising titanium dioxide nanocrystals. By subjecting the titanium dioxide nanocrystals to thermal hydrogen reduction treatment, defects such as oxygen vacancies can be generated on their surface, thereby obtaining a tube-shaped carrier transport thin film with oxygen-vacancy-rich surfaces. This film is more conducive to electron enrichment, enhancing electron solubility, conductivity, and charge transport at the bulk phase and interface. This invention solves the limitations imposed by zinc oxide nanoparticles as electron transport layer materials on the materials, preparation conditions, and dissolving solvents of other layers in the device, facilitating structural optimization and preparation method optimization of the device, thereby resulting in a light-emitting diode with better overall performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carrier transport thin film technology, and particularly relates to a method for preparing a carrier transport thin film and a light-emitting diode. Background Technology

[0002] Zinc oxide is a commonly used material for electron transport layers. Its popularity in the electron transport materials field stems from two main reasons: firstly, its preparation method is simple, low-cost, non-toxic, and environmentally friendly; secondly, zinc oxide is a wide bandgap material, resulting in electron transport layers with high transmittance, high electron mobility, and high carrier concentration. However, using only zinc oxide nanoparticles as the electron transport material limits the materials, preparation conditions, and solvents available for other layers in the resulting device. Therefore, developing other high-performance electron transport materials is particularly important.

[0003] In recent years, inorganic semiconductors have become a popular research topic as electron transport layers. Among them, titanium dioxide (TiO2) is a wide bandgap semiconductor material that has attracted much attention from researchers due to its advantages such as quantum confinement effect, size effect, and superior fluorescence properties. Titanium dioxide nanomaterials have shown great potential in the research of photocatalysis, sensors, transparent electrodes, diodes, and solar cells. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing a carrier transport thin film and a light-emitting diode, aiming to solve the technical problems of non-radiative Auger recombination caused by excessive electron injection in existing zinc oxide carrier transport thin films.

[0005] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows:

[0006] On one hand, the present invention provides a method for preparing a carrier transport thin film, which includes the following steps:

[0007] Provides a charge carrier transport material and a solvent, wherein the charge carrier transport material comprises titanium dioxide nanocrystals;

[0008] The charge carrier transport material is dispersed in the solvent to form a dispersion;

[0009] The dispersion was subjected to thermal hydrogen reduction treatment in a hydrogen atmosphere to obtain a carrier transport thin film.

[0010] On the other hand, the present invention provides a light-emitting diode, wherein the electron transport layer is a carrier transport thin film prepared by the method for preparing the carrier transport thin film provided by the present invention.

[0011] Finally, the present invention provides a method for fabricating a light-emitting diode, comprising the following steps:

[0012] An anode is provided, and a hole-functional layer is prepared on the surface of the anode;

[0013] A light-emitting layer is prepared on the surface of the hole-functional layer opposite to the anode;

[0014] A titanium dioxide nanocrystal dispersion is provided, and the dispersion is coated on the surface of the light-emitting layer opposite to the hole-functional layer. After thermal hydrogen reduction treatment, an electron transport layer is obtained.

[0015] A cathode is fabricated on the surface of the electron transport layer opposite to the light-emitting layer to obtain a light-emitting diode;

[0016] or

[0017] A cathode and a titanium dioxide nanocrystal dispersion are provided. The dispersion is coated on the surface of the cathode and subjected to thermal hydrogen reduction treatment to obtain an electron transport layer.

[0018] A light-emitting layer is prepared on the surface of the electron transport layer opposite to the cathode;

[0019] A hole-functional layer is prepared on the surface of the light-emitting layer opposite to the electron transport layer;

[0020] An anode is fabricated on the surface of the hole functional layer opposite to the light-emitting layer to obtain a light-emitting diode.

[0021] The method for preparing a carrier transport thin film provided by this invention only requires dispersing a light-emitting diode carrier transport material containing titanium dioxide nanocrystals in a solvent to form a dispersion, and then subjecting the dispersion to thermal hydrogen reduction treatment to obtain the carrier transport thin film. This method is simple to operate, easy to control, and conducive to large-scale production. Titanium dioxide is a wide-bandgap inorganic semiconductor material with high electron mobility, low dielectric constant and density, good light transmittance, and stable physical and chemical properties. Using a material containing titanium dioxide nanocrystals to prepare a carrier transport thin film can result in a film with high conductivity and carrier transport performance. It also solves the limitations imposed by zinc oxide nanoparticles as an electron transport layer material on the materials, preparation conditions, and solvents used in other layers of the device, facilitating device structure optimization and preparation method optimization. Furthermore, zinc oxide carrier transport thin films suffer from non-radiative Auger recombination due to excess electron injection. This invention addresses this by subjecting titanium dioxide nanocrystals to thermal hydrogen reduction treatment, which generates defects such as oxygen vacancies on their surface, thereby obtaining a carrier transport thin film with oxygen-rich surfaces. The carrier transport film after thermal hydrogen reduction treatment is more conducive to electron enrichment, which can enhance electron solubility, conductivity and charge transport at the bulk phase and interface.

[0022] The light-emitting diode provided by this invention contains titanium dioxide nanocrystals in its electron transport layer. This solves the limitations imposed by zinc oxide nanoparticles on the materials, preparation conditions, and dissolution solvents of other layers in the device when zinc oxide nanoparticles are used as the electron transport layer material. This facilitates the optimization of the device structure and preparation method. Furthermore, the electron transport layer undergoes thermal hydrogen reduction treatment, which generates defects such as oxygen vacancies on its surface, making it more conducive to electron enrichment. This enhances electron solubility, conductivity, and charge transport at the bulk phase and interface, thereby giving the resulting light-emitting diode better overall performance.

[0023] The method for fabricating light-emitting diodes provided by this invention obtains an electron transport layer by coating a titanium dioxide nanocrystal dispersion. This solves the limitations imposed by zinc oxide nanoparticles as electron transport layer materials on the materials, fabrication conditions, and dissolving solvents of other layers in the device, facilitating structural optimization and fabrication method optimization. Thermal hydrogen reduction treatment generates defects such as oxygen vacancies on the surface of the resulting electron transport layer, which is more conducive to electron enrichment, enhancing electron concentration, conductivity, and charge transport at the bulk and interface phases, thereby giving the resulting light-emitting diode better overall performance. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0025] Figure 1 This is a flowchart illustrating the fabrication process of a carrier transport thin film according to one embodiment of the present invention;

[0026] Figure 2 This is a schematic diagram of the structure of a light-emitting diode provided in one embodiment of the present invention;

[0027] Figure 2 The markings in the text are as follows:

[0028] 10-Cathode; 20-Electron transport layer; 30-Light emission layer; 40-Hole functional layer; 50-Anode. Detailed Implementation

[0029] To make the objectives, technical solutions, and technical effects of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. The embodiments described below are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art in conjunction with the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed; where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0030] In the description of this invention, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0031] In the description of this invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0032] It should be understood that the weights of the relevant components mentioned in the embodiments of this invention can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this invention is within the scope of this invention. Specifically, the weights mentioned in the embodiments of this invention can be well-known units of mass in the chemical industry, such as μg, mg, g, and kg.

[0033] Furthermore, unless the context explicitly uses it otherwise, the singular form of a word should be understood as including the plural form of that word. The terms "comprising" or "having" are intended to specify the presence of a feature, quantity, step, operation, element, part, or combination thereof, but are not intended to exclude the presence or possible addition of one or more other features, quantities, steps, operations, elements, parts, or combinations thereof.

[0034] like Figure 1 As shown, this embodiment of the invention provides a method for preparing a carrier transport thin film, which includes the following steps:

[0035] S1. Provide carrier transport materials and solvents, wherein the carrier transport materials include titanium dioxide nanocrystals;

[0036] S2. Disperse the charge carrier transport material in a solvent to form a dispersion;

[0037] S3. The dispersion is subjected to thermal hydrogen reduction treatment in a hydrogen atmosphere to obtain a light-emitting diode carrier transport film.

[0038] The method for preparing a light-emitting diode (LED) carrier transport film provided in this invention only requires dispersing the LED carrier transport material containing titanium dioxide nanocrystals in a solvent to form a dispersion, and then subjecting the dispersion to thermal hydrogen reduction treatment to obtain the LED carrier transport film. This method is simple to operate, easy to control, and conducive to large-scale production. Titanium dioxide is a wide-bandgap inorganic semiconductor material with high electron mobility, low dielectric constant and density, good light transmittance, and stable physical and chemical properties. Using a material containing titanium dioxide nanocrystals to prepare a carrier transport film can result in a film with high conductivity and carrier transport performance. It also solves the limitations imposed by zinc oxide nanoparticles as an electron transport layer material on the materials, preparation conditions, and solvents used in other layers of the device, facilitating device structure optimization and preparation method optimization. Furthermore, zinc oxide carrier transport films suffer from non-radiative Auger recombination due to excess electron injection. This invention addresses this by subjecting titanium dioxide nanocrystals to thermal hydrogen reduction treatment, which generates defects such as oxygen vacancies on their surface, thereby obtaining a carrier transport film with oxygen-rich surfaces. The carrier transport film after thermal hydrogen reduction treatment is more conducive to electron enrichment, which can enhance electron solubility, conductivity and charge transport at the bulk phase and interface.

[0039] Specifically, in S1, the titanium dioxide nanocrystals in the carrier transport material provided in this embodiment of the invention can be titanium dioxide nanocrystals existing in the art, and preferably titanium dioxide nanocrystals prepared by the following preparation method:

[0040] S11 provides titanate esters, reaction inhibitors, and alcohol solvents;

[0041] S12. Titanate ester, reaction inhibitor and alcohol solvent are mixed and treated. Titanate ester is hydrolyzed to obtain titanium dioxide nanocrystals.

[0042] Specifically, in S11, titanate ester is used as a raw material for preparing titanium dioxide nanocrystals. Titanium dioxide nanocrystals can be obtained by hydrolyzing titanate ester via a sol-gel method. In some embodiments, titanate ester is selected from tetrabutyl titanate and / or tetraisopropyl titanate.

[0043] The hydrolysis rate of titanate esters is very fast. To prevent the hydrolysis reaction from occurring too quickly and causing uneven distribution of the resulting titanium dioxide nanocrystals, a reaction inhibitor is added to suppress the hydrolysis rate of the titanate ester. In some embodiments, the reaction inhibitor is selected from at least one of acetic acid, dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid, alcohols, ethers, and weak organic bases, preferably at least one of acetic acid, ethanol, and diethanolamine. These three substances have the best inhibitory effect on the hydrolysis reaction, which is beneficial for obtaining titanium dioxide nanocrystals with uniform particle size.

[0044] In these embodiments of the invention, alcohol solvents are used both as dispersion media for titanate esters and to absorb water from the air for the hydrolysis reaction. In some embodiments, the alcohol solvent is selected from at least one of ethanol, isopropanol, ethylene glycol, and butanol, with ethanol being preferred. This is because ethanol can serve as both a dispersion medium and an inhibitor of the titanate ester hydrolysis reaction.

[0045] In step S12, the method for mixing the titanate ester, reaction inhibitor, and alcohol solvent can employ conventional methods in the art, including but not limited to stirring and ultrasonication. In some embodiments, during the mixing process, the titanate ester and reaction inhibitor are mixed in a molar ratio of (1-10):1 to make the resulting titanium dioxide nanocrystals more uniform in size. If there is too much reaction inhibitor, the pH of the reaction system may be too low, affecting the crystallinity of the resulting titanium dioxide nanocrystals, leading to poor crystallinity, severe internal carrier leakage, increased charge transfer resistance, and hindering charge transport. Conversely, if there is too little reaction inhibitor, the pH of the reaction system will be too high, resulting in excessively large titanium dioxide nanocrystal particles.

[0046] In some embodiments, when mixing titanate, reaction inhibitor, and alcohol solvent, a nonionic surfactant is also added to wet the surface of the titanate and the resulting titanium dioxide nanocrystals, allowing for complete hydrolysis of the titanate and increasing the surface tension of the resulting titanium dioxide nanocrystals, thus making their dispersion more uniform. Specifically, a polyoxyethylene-type nonionic surfactant is selected, including but not limited to at least one of octylphenyl polyoxyethylene ether (Triton X-100), nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, and dodecylphenol polyoxyethylene ether. It is important to emphasize that the surfactant added in the embodiments of the present invention must be a nonionic surfactant, because the cations or anions inherent in ionic surfactants may remain on the surface of the resulting titanium dioxide nanocrystals and cannot be removed, which is not only detrimental to the subsequent heat treatment process but may also cause impurities in the titanium dioxide nanocrystals, affecting their performance.

[0047] A titanium dioxide precursor solution is obtained by mixing titanate, a reaction inhibitor, and an alcohol solvent. This solution is then stirred in air, allowing trace amounts of water from the air to enter the alcohol solvent and react with the titanate, causing hydrolysis of the titanate to form titanium dioxide nanocrystals. During this process, the reaction rate is suppressed by the reaction inhibitor to obtain uniform titanium dioxide nanocrystal particles. In some embodiments, the titanium dioxide precursor solution obtained by mixing the titanate, reaction inhibitor, and alcohol solvent is diluted 5-100 times with an alcohol solvent to increase the contact area with water and further regulate the hydrolysis reaction rate, avoiding an excessively fast or slow reaction.

[0048] The titanium dioxide nanocrystals prepared by the method provided in this invention have an average particle size of 7 nm to 11 nm. If the titanium dioxide nanocrystal particles are too large, the contact between the particles becomes poor, which can easily lead to increased interfacial charge transfer resistance and reduced charge transport efficiency. If the titanium dioxide nanocrystal particles are too small, the crystallization performance is poor, and the internal charge leakage of the particles is serious. Specifically, typical, but not limiting, average particle sizes of titanium dioxide nanocrystals are 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, 10 nm, 10.5 nm, and 11 nm.

[0049] The titanium dioxide nanocrystals prepared according to the preparation methods provided in embodiments S11-S12 of the present invention have a more uniform particle distribution. When forming a carrier transport thin film, the film can be made more dense and uniform, and has better carrier transport performance.

[0050] A solvent is used to disperse the charge carrier transport material to form a dispersion for subsequent film formation. In some embodiments, the solvent is selected from at least one of ethanol, isopropanol, and butanol.

[0051] In S2, the charge carrier transport material is dispersed in a solvent to form a dispersion, wherein the content of titanium dioxide nanocrystals in the resulting dispersion is 10 mg / mL-60 mg / mL. If the content is too high, the film layer may be too thick when forming the charge carrier transport film, resulting in increased resistance and affecting charge transport; if the content is too low, the resulting charge carrier transport film is too thin, the electron concentration is high, and it is easy for the hole transport layer to accumulate, leading to severe nonradiative recombination problems. Specifically, the typical, but not limiting, content of titanium dioxide nanocrystals in the dispersion is 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 40 mg / mL, 45 mg / mL, 50 mg / mL, 55 mg / mL, and 60 mg / mL.

[0052] In S3, the dispersion is heat-treated by thermal hydrogen reduction in a hydrogen atmosphere. Thermal hydrogen reduction facilitates the generation of defects such as oxygen vacancies on the surface of the titanium dioxide nanocrystals, thereby obtaining a carrier transport film rich in oxygen vacancies. This oxygen-vacancy-rich carrier transport film is beneficial for electron enrichment, enhancing the electron solubility and conductivity of the carrier transport film, and also improving charge transport at the bulk phase and interface. In some embodiments, the hydrogen pressure during thermal hydrogen reduction is 1.5 MPa–2.0 MPa. Specifically, typical, but not limiting, hydrogen pressures are 1.5 MPa, 1.6 MPa, 1.7 MPa, 1.8 MPa, 1.9 MPa, and 2.0 MPa.

[0053] In some embodiments, when the dispersion is subjected to thermal hydrogen reduction treatment, the temperature of the thermal hydrogen reduction treatment is 400°C-500°C, and the time of the thermal hydrogen reduction treatment is 30 min-60 min, so as to improve the compactness of the resulting quantum dot light-emitting diode carrier transport film. Specifically, typical, but not limiting, thermal hydrogen reduction treatment temperatures are 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, and 500°C; typical, but not limiting, thermal hydrogen reduction treatment times are 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, and 60 min.

[0054] The carrier transport thin film prepared in this embodiment of the invention has a thickness of 20nm-40nm. If the thickness is too thin, it is easy to cause too much electron injection and charge imbalance; if the thickness is too thick, the charge transfer resistance at the film interface is large, which is not conducive to carrier injection. Specifically, typical, but not limiting, thicknesses are 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, and 40nm.

[0055] The carrier transport thin film preparation method and the carrier transport thin film prepared by the embodiments of the present invention can be used as an electron transport layer for organic light-emitting devices (such as OLEDs) or as an electron transport layer for quantum dot light-emitting diodes (QLEDs).

[0056] This invention also provides a light-emitting diode (LED) including an electron transport layer, which is a carrier transport thin film prepared by the method for preparing a carrier transport thin film provided in this invention. In some embodiments, the LED further includes an anode and a cathode disposed opposite to each other, and a hole functional layer and a light-emitting layer stacked between a bottom electrode and a top electrode, with the electron transport layer disposed between the cathode and the light-emitting layer.

[0057] The light-emitting diode provided in this invention contains titanium dioxide nanocrystals in its electron transport layer. This solves the limitations imposed by zinc oxide nanoparticles on the materials, preparation conditions, and dissolving solvents of other layers in the device when zinc oxide nanoparticles are used as the electron transport layer material. This facilitates the optimization of the device structure and preparation method, thereby enabling the resulting light-emitting diode to have better overall performance.

[0058] In some embodiments, the light-emitting diode may further include a substrate, with a bottom electrode or a top electrode disposed on the substrate. In some specific embodiments, the substrate may include rigid substrates such as glass, metal foil, or other commonly used rigid substrates, or flexible substrates such as polyimide (PI), polycarbonate (PC), polystyrene (PS), polyethylene (PE), polyvinyl chloride (PV), polyvinylpyrrolidone (PVP), polyethylene terephthalate (PET), and similar materials, which mainly serve a supporting function.

[0059] The anode can be made of common anode materials and thicknesses, and the embodiments of the present invention are not limited thereto. In some embodiments, the anode material can be indium tin oxide (ITO), indium zinc oxide (IZO) conductive glass or indium tin oxide and indium zinc oxide electrodes, or other metallic materials such as gold, silver, aluminum, etc.

[0060] The cathode can use common cathode materials and thicknesses, and the embodiments of the present invention are not limited thereto. In some embodiments, the cathode material includes at least one of a metallic material, a conductive metal oxide, and a conductive carbon material. The metallic material includes, but is not limited to, at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, and Mg; the conductive carbon material includes, but is not limited to, at least one of graphite, carbon nanotubes, graphene, and carbon fibers; the conductive metal oxide can be a doped metal oxide or an undoped metal oxide, including, but not limited to, at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO, and AMO. In addition, the conductive metal oxide can also be a composite electrode formed by sandwiching metal between doped or undoped transparent metal oxides. These composite electrodes include, but are not limited to, at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2.

[0061] In some embodiments, the material of the light-emitting layer is quantum dots, and correspondingly, the resulting light-emitting diode is a quantum dot light-emitting diode.

[0062] The light-emitting diodes provided in this embodiment of the invention can be either upright or inverted. When thermal hydrogen treatment is specifically employed, an inverted light-emitting diode is preferred. Figure 2 As shown, the inverted light-emitting diode provided in this embodiment of the invention includes, from bottom to top, a cathode 10, an electron transport layer 20 disposed on the cathode surface, a light-emitting layer 30 disposed on the surface of the electron transport layer 20, a hole functional layer 40 disposed on the surface of the light-emitting layer 30, and an anode 50 disposed on the surface of the hole functional layer 40. The electron transport layer 20 is a carrier transport thin film prepared by the method provided in this embodiment of the invention. Because this embodiment of the invention manufactures the light-emitting diode in an inverted configuration, the other layers are prepared after the electron transport layer, thereby avoiding the destruction of small organic molecules in the other layers during the high-temperature thermal hydrogen treatment process, and ensuring the performance of the light-emitting diode.

[0063] In the light-emitting diodes of this invention, the materials used for the hole functional layer and the light-emitting layer can both be conventional materials in the art, and the thicknesses of the hole functional layer and the light-emitting layer can also be conventional thicknesses in the art. In some embodiments, the thickness of the electron transport layer is 20nm-40nm. If the thickness is too thin, it is easy to cause too much electron injection and charge imbalance; if the thickness is too thick, the charge transfer resistance at the thin film interface is large, which is not conducive to carrier injection. Specifically, typical, but not limiting, thicknesses of the electron transport layer are 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, 31nm, 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, and 40nm.

[0064] The light-emitting diodes provided in this embodiment of the invention can be prepared by the following method.

[0065] Accordingly, embodiments of the present invention provide a method for fabricating a light-emitting diode, which includes the following steps:

[0066] S21. Provide an anode and prepare a hole-functional layer on the anode surface;

[0067] S22. Prepare a light-emitting layer on the surface of the hole functional layer away from the anode;

[0068] S23. Provide a titanium dioxide nanocrystal dispersion, coat the dispersion on the surface of the light-emitting layer away from the hole functional layer, and then perform thermal hydrogen annealing to obtain an electron transport layer.

[0069] S24. A cathode is fabricated on the surface of the electron transport layer away from the light-emitting layer to obtain a light-emitting diode;

[0070] or

[0071] S31. Provide a cathode and a titanium dioxide nanocrystal dispersion, coat the dispersion on the surface of the cathode, and perform thermal hydrogen annealing to obtain an electron transport layer;

[0072] S32. Prepare a light-emitting layer on the surface of the electron transport layer away from the cathode;

[0073] S33. Prepare a hole functional layer on the surface of the light-emitting layer away from the electron transport layer;

[0074] S34. An anode is prepared on the surface of the hole functional layer away from the light-emitting layer to obtain a light-emitting diode.

[0075] Among them, the light-emitting diodes prepared by S21-S24 are positive light-emitting diodes, and the light-emitting diodes prepared by S31-S34 are inverted light-emitting diodes.

[0076] In the method for preparing a light-emitting diode provided in this embodiment of the invention, except for S23 and S31, where the method for forming the electron transport layer is thermal hydrogen annealing and the material for forming the electron transport layer includes titanium dioxide nanocrystals, the materials and preparation methods of the other layers are conventional methods in the art, the thickness of each layer is a conventional thickness in the art, and the thickness of the electron transport layer is as described above, and will not be repeated here.

[0077] The method for fabricating a light-emitting diode (LED) provided in this invention involves coating an electron transport layer with a titanium dioxide nanocrystal dispersion. This overcomes the limitations imposed by zinc oxide nanoparticles as the electron transport layer material on the materials, fabrication conditions, and solvents used in other layers of the device, facilitating structural optimization and fabrication method optimization. Thermal hydrogen reduction treatment generates defects such as oxygen vacancies on the surface of the resulting electron transport layer, further enhancing electron enrichment, electron density, conductivity, and charge transport at the bulk and interface phases, thereby improving the overall performance of the resulting LED.

[0078] To enable those skilled in the art to clearly understand the above-described implementation details and operations of the present invention, and to demonstrate the significant advancements in the carrier transport materials and light-emitting diodes of the present invention, the following examples illustrate the above technical solutions.

[0079] Example 1

[0080] This embodiment provides a method for preparing a carrier transport thin film, including the following steps:

[0081] (11) Mix 1.4 ml TX-100 with 7.6 ml anhydrous ethanol, add 24 mmol acetic acid and 24 mmol tetraisopropyl titanate, stir vigorously at room temperature for 10 min to obtain TiO2 precursor solution, dilute TiO2 precursor solution 10 times with anhydrous ethanol, place in air, continue stirring for 30 min to grow slowly to obtain titanium dioxide nanocrystal solution with an average particle size of 9 nm and a content of 20 mg / mL;

[0082] (12) Spin-coat the titanium dioxide nanocrystal solution obtained in step (11) onto a clean IZO glass substrate and place it in a tube furnace with a hydrogen pressure of 1.5 MPa and a temperature of 500 °C for annealing for 30 min to obtain a carrier transport film with oxygen-rich vacancies on the surface, which is the electron transport layer of the quantum dot light-emitting diode with a thickness of 36 nm.

[0083] Example 2

[0084] This embodiment provides a method for preparing a carrier transport thin film, including the following steps:

[0085] (21) Mix 1.4 ml of nonylphenol polyoxyethylene ether with 7.6 ml of anhydrous ethanol, add 24 mmol of acetic acid and 24 mmol of tetraisopropyl titanate, stir vigorously at room temperature for 10 min to obtain TiO2 precursor solution, dilute TiO2 precursor solution 20 times with anhydrous ethanol, place in air, continue stirring for 30 min to grow slowly to obtain titanium dioxide nanocrystal solution with an average particle size of 11 nm and a content of 10 mg / mL.

[0086] (22) The titanium dioxide nanocrystal solution obtained in step (21) is spin-coated onto a clean IZO glass substrate and placed in a tube furnace with a hydrogen pressure of 2 MPa and a temperature of 450 °C for annealing for 30 min to obtain a carrier transport film with oxygen-rich vacancies on the surface, which is the electron transport layer of the quantum dot light-emitting diode with a thickness of 28 nm.

[0087] Comparative Example 1

[0088] This comparative example provides a method for preparing a carrier transport thin film, including the following steps:

[0089] (31) Mix 1.4 ml TX-100 with 7.6 ml anhydrous ethanol, add 24 mmol acetic acid and 24 mmol tetraisopropyl titanate, stir vigorously at room temperature for 10 min to obtain TiO2 precursor solution, dilute TiO2 precursor solution 10 times with anhydrous ethanol, place in air, continue stirring for 30 min to grow slowly to obtain titanium dioxide nanocrystal solution with an average particle size of 9 nm and a content of 20 mg / mL;

[0090] (32) Spin-coat the titanium dioxide nanocrystal solution obtained in step (31) onto a clean IZO glass substrate and anneal it in a tube furnace at 450°C for 30 min to obtain a carrier transport film, which is the electron transport layer of the quantum dot light-emitting diode with a thickness of 36 nm.

[0091] Comparative Example 2

[0092] This comparative example provides a method for preparing a carrier transport thin film, including the following steps:

[0093] (41) Mix 1.4 ml of nonylphenol polyoxyethylene ether with 7.6 ml of anhydrous ethanol, add 24 mmol of acetic acid and 24 mmol of tetraisopropyl titanate, stir vigorously at room temperature for 10 min to obtain TiO2 precursor solution, dilute TiO2 precursor solution 20 times with anhydrous ethanol, place in air, continue stirring for 30 min to grow slowly to obtain titanium dioxide nanocrystal solution with an average particle size of 11 nm and a content of 10 mg / mL.

[0094] (42) Spin-coat the titanium dioxide nanocrystal solution obtained in step (41) onto a clean IZO glass substrate and anneal it in a tube furnace at 450°C for 30 min to obtain a carrier transport film, which is the electron transport layer of the quantum dot light-emitting diode with a thickness of 28 nm.

[0095] Experimental Example

[0096] The resistivity of the electron transport layer obtained in Examples 1-2 and Comparative Examples 1-2 was measured using the four-probe method, and the conductivity was calculated using the formula σ=1 / ρ. The results are shown in Table 1.

[0097] Table 1. Conductivity of the electron transport layers obtained in Examples 1-2 and Comparative Examples 1-2

[0098] Electrical conductivity (S / cm) Example 1 <![CDATA[5.96×10 -4 ]]> Example 2 <![CDATA[6.83×10 -4 ]]> Comparative Example 1 <![CDATA[2.74×10 -8 ]]> Comparative Example 2 <![CDATA[4.77×10 -8 ]]>

[0099] As can be seen from Examples 1 and 2 and Table 1, the embodiments of the present invention can not only use titanium dioxide nanocrystals as the material of the electron transport layer of quantum dot light-emitting diodes, but also, by performing hot hydrogen treatment annealing on the titanium dioxide nanocrystal solution, the surface of the resulting electron transport layer is rich in oxygen vacancies due to the lack of oxygen during the annealing process, thus exhibiting higher conductivity.

[0100] The above are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing a carrier transport thin film, characterized in that, Includes the following steps: Provides a charge carrier transport material and a solvent, wherein the charge carrier transport material comprises titanium dioxide nanocrystals; The charge carrier transport material is dispersed in the solvent to form a dispersion; The dispersion is subjected to thermal hydrogen reduction treatment in a hydrogen atmosphere to obtain a carrier transport film with oxygen vacancies on its surface, wherein the hydrogen pressure of the thermal hydrogen reduction treatment is 1.5 MPa-2.0 MPa.

2. The method for preparing the carrier transport thin film according to claim 1, characterized in that, The temperature of the thermal hydrogen reduction treatment is 400℃-500℃, and the time of the thermal hydrogen reduction treatment is 30min-60min.

3. The method for preparing the carrier transport thin film according to claim 1, characterized in that, The titanium dioxide nanocrystals have an average particle size of 7nm-11nm; and / or The content of titanium dioxide nanocrystals in the dispersion is 10 mg / mL to 60 mg / mL.

4. The method for preparing the carrier transport thin film according to any one of claims 1-3, characterized in that, The preparation method of the titanium dioxide nanocrystals includes the following steps: Provides titanates, reaction inhibitors, and alcohol solvents; The titanate, the reaction inhibitor, and the alcohol solvent are mixed and treated, and the titanate is hydrolyzed to obtain titanium dioxide nanocrystals.

5. The method for preparing the carrier transport thin film according to claim 4, characterized in that, The titanate is selected from at least one of tetrabutyl titanate and tetraisopropyl titanate; and / or The reaction inhibitor is selected from at least one of acetic acid, dilute hydrochloric acid, dilute sulfuric acid, dilute nitric acid, alcohols, ethers, and organic bases; and / or The alcohol solvent is selected from at least one of ethanol, isopropanol, ethylene glycol, and butanol.

6. The method for preparing the carrier transport thin film according to any one of claims 1-3, characterized in that, The thickness of the carrier transport film is 20nm-40nm; and / or The solvent is selected from at least one of ethanol, isopropanol, and butanol.

7. A light-emitting diode, characterized in that, Includes an electron transport layer, wherein the electron transport layer is a carrier transport thin film prepared by the method described in any one of claims 1-6.

8. The light-emitting diode according to claim 7, characterized in that, It also includes an anode and a cathode arranged opposite to each other, and a hole functional layer and a light-emitting layer stacked between the anode and the cathode, wherein the electron transport layer is disposed between the light-emitting layer and the cathode.

9. A method for fabricating a light-emitting diode, characterized in that, Includes the following steps: An anode is provided, and a hole-functional layer is prepared on the surface of the anode; A light-emitting layer is prepared on the surface of the hole-functional layer opposite to the anode; A titanium dioxide nanocrystal dispersion is provided. The dispersion is coated on the surface of the light-emitting layer opposite to the hole-functional layer. After thermal hydrogen reduction treatment, an electron transport layer with oxygen vacancies on the surface is obtained. The hydrogen pressure of the thermal hydrogen reduction treatment is 1.5 MPa-2.0 MPa. A cathode is fabricated on the surface of the electron transport layer opposite to the light-emitting layer to obtain a light-emitting diode.

Citation Information

Patent Citations

  • Method for preparing nano titanium dioxide by sol process at low temperature

    CN102674452A

  • Preparation method of conductive and light transmittance perovskite quantum dot thin film

    CN109301093A